Osteopathic treatment of infants with infantile colic/excessive crying: a prospective, multicentric, randomized controlled trial and nested observational trial - Florian Schwerla; Marlen Zimmer; Janine Göpfert; Petra Laux; Simone Langenmair; Michaela Rütz; Karl-Ludwig Resch (BMC Pediatrics)
Abstract Background Colic in infants is defined as excessive crying in an otherwise healthy and thriving baby. Colic is a common but poorly understood and often frustrating problem for caregivers. Objective To study whether osteopathic treatments of infants with infantile colic / excessive crying (IC/EC) have an impact on the subjectively perceived psychological stress of caregivers compared to usual care. Methods The study was designed as a prospective, multicenter, randomized controlled trial. Infants aged 1 week to 3 months and who met Rome IV criteria for IC/EC were included. By means of external randomization, infants were allocated to an intervention group or a control group. Infants in the intervention group received three osteopathic treatments at intervals of one weeks. The treatments were custom-tailored and based on osteopathic principles. Controls received their osteopathic treatment after a 3 week untreated period. The primary outcome parameter was the assessment of parental psychological stress (three questions), measured using a numeric rating scale (NRS; 0–10). Furthermore, the average daily crying time (measured using the Likert scale), the crying intensity (measured using the NRS) and the parents' self-confidence (measured using the Karitane Parenting Confidence Scale) were assessed. Results A total of 103 infants (average age 39.4 ±19.2 days) were included, 52 in the intervention group and 51 in the control group. An inter-group comparison of changes revealed clinically relevant improvements in favor of the intervention group for the main outcome – parameter psychological stress – for all 3 questions (e.g., for question 2 respectively 3, NRS: between group difference of means 3.5; 95% CI: 2.6 to 4.4; p < 0.001). For the secondary outcome parameters of crying intensity and crying time/day, the changes were of similar magnitude. Conclusion Three osteopathic treatments given over a period of two weeks led to statistically significant and clinically relevant positive changes of parental psychological stress. Trial registration German Clinical Trials Register: DRKS00025867, registration date 10.08.21.